Synthesis and Characterization of Some Graphene Oxide Powders Used as Additives in Hydraulic Mortars - Doina Prodan; Marioara Moldovan; Gabriel Furtos; Codruța Saroși; Miuța Filip; Ioana Perhaița; Rahela Carpa; Maria Popa; Stanca Cuc; Simona Varvara; Dorin Popa (Applied Sciences, 2021)
Various powders of graphene oxide (GO), GO with silver (GO-Ag) and zinc oxide (GO-ZnO) were obtained. The powders were silanized with (3-aminopropyl) triethoxysilane (APTES) aiming to be used, in a future stage, as additives in the hydraulic lime mortars composition. The powders were characterized by Fourier Transform Infrared Spectrometry (FTIR) and Scanning Electron Microscopy (SEM) before and after the silanization process. GO, GO-Ag, GO-Ag-APTES, GO-ZnO and GO-ZnO-APTES powders were also investigated by Thermogravimetric Analysis (TG/DTA) and Ultraviolet–Visible Spectroscopy (UV-Vis). Likewise, the antibacterial effect of powders against five bacterial strains was evaluated. The peaks associated to the functional groups from GO, GO-APTES, GO-Ag, GO-Ag-APTES, GO-ZnO and GO-ZnO-APTES powders were identified by FTIR analysis. The mass losses of powders, analyzed by TG/DTA were lower than those recorded for GO. By UV-VIS analysis, maxima corresponding to the electronic π-π * and n-π * transitions were recorded. SEM images highlighted the lamellar and layered structure of GO, but also the presence of Ag and Zn nanoparticles on the surface of graphene sheets. All these results confirm the presence of Ag/ZnO/APTES on the GO. The antibacterial effect evaluated by recording the diameter of the inhibition zone ranged between 12–22 mm.